Estimation of Finite Population Mean in the Presence of Nonresponse on Both Study and Auxiliary Variables - Abubakari, Iddrisu; Jakperik, Dioggban; Nasiru, Suleman (Universitas Brawijaya, 2026)
The study investigated the challenge of estimating the expected value of finite population of the main variable using supplementary data from under nonresponse. The proposed estimator was then compared with competing estimators. Analytical and empirical findings, demonstrate that the proposed ratio estimator, based on a third order approximation, exhibits higher efficiency than competing estimators, especially with large samples. The performance of the proposed ratio estimator, like other bias reduction estimators is enhanced for large samples.